Corporate social responsibility in European cooperative banks: the French specificity. (6th July 2010) - Paulet, Elisabeth
This paper intends to use a conceptual paradigm to discuss the ambiguity of corporate governance while issuing shares to maintain their capital adequacy for European cooperative banks. It thus provides theoretical evidence for the arbitrage between stakeholder and shareholder control for these particular institutions. Therefore, we propose, firstly, to trace the historical development of the European banking system, particularly that of the universal institutions, with a view to identifying their position in the European context. Secondly, we demonstrate that, although having followed the same trend, cooperative banks intend to stand by their primary objective: to collect individual savings and to protect their cooperative statutes. Finally, based on several interviews held with top managers, we discuss the issue for French cooperative banks of their introduction on the financial markets to maintain their equity level and its consequence: the delicate arbitrage as regards the definition of corporate governance.